Cell to Cell Signalling via Exosomes Through esRNA - Lotvall, Jan (Landes Bioscience, 2007)
Exosomes are small vesicles of endosomal origin that can be released by many different cells to the microenvironment. Exosomes have been shown to participate in the immune system, by mediating antigen presentation. We have recently shown the presence of both mRNA and microRNA in exosomes, specifically in exosomes derived from mast cells. This RNA can be transferred between one mast cell to another, most likely through fusion of the exosome to the recipient cell membrane. The delivered RNA is functional, as the mRNA can lead to translation of new proteins in a recipient cell. The RNA shuttled between cells via exosomes is called esRNA. We propose that several types of exosomes may exist, and that an additional function of exosomes is to communicate to neighbouring cells through delivery of RNA-signals.